Study of ATRX and p53 Mutation in Astrocytomas and Its Role in Tumor Grading - R S, Sasirega; Chandramouleeswari, K; Regis, M. Dougul (Annals of Pathology and Laboratory Medicine, 2025)
Background: Astrocytomas are the most common primary brain malignancies. They come under a large group of clinically, pathologically and genetically diverse glial neoplasms designated as diffuse gliomas. The majority of IDH mutant astrocytomas also harbour ATRX and p53 mutations. The aim of the present study is to analyse ATRX and p53 mutation in astrocytomas by immunohistochemistry and its role in tumor classification and grading. Methods: The cross-sectional study was conducted in the department of neuropathology, Madras Medical College for a period of 18 months from December 2022 to May 2024. A total of 54 cases with clinical suspicion and radiological evidence of astrocytoma were included in the study. Immunohistochemical analysis of ATRX and p53 were done and expressions were evaluated. Results: Among 54 cases, 44.5% of them are grade 2 followed by 25.9% in grade 4, 18.5% in grade 3 and 11.1% in grade 1. Correlation with age, gender and anatomical location were done. Loss of ATRX expression was significantly associated with astrocytomas (p<0.001), p53 mutation was lost in 9.3% of cases (p=0.41). Conclusion: ATRX is an important immunohistochemical marker in astrocytomas, the loss of which is associated with higher grades, hence this can be used as a prognostic marker in astrocytomas. P53 mutation in astrocytomas may enable tumor cell survival in setting of ATRX loss.